Crocodile burning - Williams, Michael (New York : Puffin, 1994)
Hoping to earn the money to get his brother out of prison, Seraki joins the cast of a musical written to express rage at conditions in their South African township. He travels to New York to perform it.
Booklist.
Notable/Best Books (A.L.A.).
School Library Journal.
Young Adult
Keywords: Blacks -- South Africa -- Fiction; Theater -- Fiction; Blacks -- South Africa -- Fiction; Theater -- Fiction; South Africa -- Fiction; South Africa -- Fiction